2018
DOI: 10.1111/hepr.13182
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with red light‐emitting diodes accelerates hepatocyte proliferation through reactive oxygen species/extracellular signal‐regulated kinase pathway

Abstract: Red LED irradiation could accelerate hepatocyte proliferation through the ROS/pERK1/2 pathway. Red LED irradiation might be a potential method to increase hepatocyte cell numbers in vitro and support cell-based transplantation in clinical work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…LED irradiation has positive effects on stimulation of neuronal growth, protection of post-ischemia skeletal muscle, protection of cardiomyocytes, acceleration of wound healing, reduction of the in ammatory response, and stimulation of cell proliferation and differentiation [3,5,7,14]. Here, we demonstrated that GLED irradiation also has an effect on the function of HLCs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…LED irradiation has positive effects on stimulation of neuronal growth, protection of post-ischemia skeletal muscle, protection of cardiomyocytes, acceleration of wound healing, reduction of the in ammatory response, and stimulation of cell proliferation and differentiation [3,5,7,14]. Here, we demonstrated that GLED irradiation also has an effect on the function of HLCs.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, light-emitting diode (LED) irradiation has been used to treat several clinical conditions, including wound healing, pain, bone regeneration and treatment of various diseases and infections [2]. We have reported that LED irradiation can result in various biological effects, such as mouse hepatocyte proliferation and colon cancer cell autophagy [3,4]. The effect of LED irradiation at different wavelengths and energy densities also improves the regenerative capacity of various types of MSC [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…PBM modulates the levels of ROS, since ROS can be produced by red light absorption by mitochondria and opsins and also by the increased mitochondrial membrane potential (MMP), which consequently enhances ATP production . Moreover, ROS induced by PBM can generate several responses: promotion of proliferation by the pERK1/2 pathway ; activation of transcription factors and signaling pathways, for example, transforming growth factor‐ β 1 (TGF‐ β 1), which is capable of differentiating human stem cells . Thus, a combination of different cell death/viability/proliferation assays should be performed to better explain this result.…”
Section: Resultsmentioning
confidence: 99%
“…Different from intense light treatment that heats the treated tissue, PBM is not mediated by a thermal effect on cells . PBM, especially using a red light source, has also been shown to stimulate hepatocyte proliferation and metabolism , fibroblast proliferation, and wound healing . On the other hand, red light PBM has been widely demonstrated to be beneficial for osteoarthritis , pain control , chemotherapy adverse effect management , and wound healing in animal models or human trials .…”
Section: Introductionmentioning
confidence: 99%